2014
DOI: 10.1534/genetics.114.170068
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Copy Number Underlies Adaptive Mutability in Bacteria

Abstract: The origin of mutations under selection has been intensively studied using the Cairns-Foster system, in which cells of an Escherichia coli lac mutant are plated on lactose and give rise to 100 Lac+ revertants over several days. These revertants have been attributed variously to stress-induced mutagenesis of nongrowing cells or to selective improvement of preexisting weakly Lac+ cells with no mutagenesis. Most revertant colonies (90%) contain stably Lac+ cells, while others (10%) contain cells with an unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…In this model, pre-existing initiator cells have a 10-fold increased lac copy number. These cells form during non-selective pre-growth and are held at a high steady state frequency (about 1 in a 1000) dictated by their rates of copy number increase and decrease (REAMS et al 2010;SANO et al 2014). After plating, selection enhances reversion by allowing initiator cells to replicate their F'lac plasmid more than their chromosome, which provides more opportunities for reversion.…”
Section: Maisnier-patin and Roth (In Preparation)mentioning
confidence: 99%
See 3 more Smart Citations
“…In this model, pre-existing initiator cells have a 10-fold increased lac copy number. These cells form during non-selective pre-growth and are held at a high steady state frequency (about 1 in a 1000) dictated by their rates of copy number increase and decrease (REAMS et al 2010;SANO et al 2014). After plating, selection enhances reversion by allowing initiator cells to replicate their F'lac plasmid more than their chromosome, which provides more opportunities for reversion.…”
Section: Maisnier-patin and Roth (In Preparation)mentioning
confidence: 99%
“…This observed distribution was like that seen for revertants accumulation in the Cairns-Foster system. The Poisson distribution suggested that revertants either form on the selection plate (CAIRNS AND FOSTER 1991) or are initiated by pre-existing copy number variants that are not subject to LuriaDelbrück fluctuation (SANO et al 2014) . In this E. coli position effect test, revertant number was increased by a lexA(Def) mutation which causes constitutive expression of dinB by SOS derepression and was reduced by removal of the dinB + from the F'lac plasmid (KIM et al 2001).…”
Section: An Extra Ectopic Chromosomal Dinb + Gene Does Not Compensatementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, fluctuation tests carried out under these conditions showed a Poisson distribution of the number of mutants, as opposed to the stochastic fluctuating number of mutants obtained by Luria and Delbruck in their experiments, suggesting that the revertants arose after plating on selective medium 5 . Proponents of the 'stress-induced mutagenesis' (SIM) model proposed that the higher mutation rate occurs in response to the growth limitation 5,7,8 , whereas opponents explained the rates in terms of slow DNA replication/cell division (hereafter termed 'cryptic growth') shaped by natural selection [9][10][11][12][13] . The renewed debate centred around whether the stressed cells induce mechanisms to cause increased DNA replication in the absence of growth, resulting in increased mutation rates, or whether cryptic growth occurs, allowing natural selection of randomly generated beneficial mutations.…”
mentioning
confidence: 99%